Comparative Advantage Of Vegetables Production In Bangladesh (Bangladesh Journal of Agricultural Research, 2011)
The study was undertaken to assess the comparative advantage of production and export of vegetables from Bangladesh. Fifty four kinds of different vegetables were exported from Bangladesh. The importing countries were mostly in the Middle East. The demand for summer vegetables was found higher than those of winter vegetables. Total export quantity was found 6046 metric tons of vegetables and earned foreign exchange of Tk. 1120 million, which was only 1.18 percent of total value of vegetable production in Bangladesh. Among the export marketing cost items, air freights charges was found highest. For all the vegetables, DRCs were observed to be less than unity implying that Bangladesh had comparative advantage in vegetable production.   Keywords: Export potential; vegetables; foreign exchange earnings DOI: http://dx.doi.org/10.3329/bjar.v36i1.9232 BJAR 2011; 36(1): 89-95